The Contours of America's Cold War - Farish, Matthew (Book collections on Project MUSE., 2010)
In The Contours of America's Cold War, Matthew Farish explores new ways of conceptualizing space as part of post-World War II American militarism. He demonstrates how the social sciences were militarized in the early Cold War period, producing spatial knowledge that was of immediate use to the state as it sought to expand its reach across the globe. Geographic knowledge generated for the Cold War was a form of power, Farish argues, and it was given an urgency in the panels, advisory boards, and study groups established to address the challenges of an atomic world.